Analytical accuracy of the handheld PICO monitoring device during emergencies. Issue 1 (January 2019) - Renier, Walter Sylvain; Erard, Koen; Sabbe, Marc; Hubloue, Ives; Verbakel, Jan Y; Aertgeerts, Bert; Buntinx, Frank
Abstract : Introduction: General practitioners (GP) use few technical devices during emergency situations. They have to recognise which patients have a life-threatening disease in order to treat or refer them appropriately. Monitoring by a wearable device could help GPs while waiting for the emergency physician to arrive. The PICO monitor is a handheld monitoring device, capable of registering five routine parameters and small enough to be carried in the GP's bag. We aim to determine the analytical accuracy of the PICO monitor in adults, comparing the recorded vital signs and ECGs of the PICO with those of a standard emergency department (ED) monitor. Methods: Adult (≥18 years) patients, admitted on two inpatient university EDs in Belgium, were recruited. We recorded the SpO2, heart rate (HR), respiration rate (RR), temperature (T°) and 5-lead ECGs. We analysed the correlation and agreement between the continuous and dichotomous variables of the PICO and the ED monitors. Results: We included 226 patients (84% of 268 approached), mean age 66 years, 61% were men. The Bland and Altman analysis confirmed the good accuracy, giving a nearly perfect agreement for SpO2 (difference —0.9%), for HR (−1.5 beats), for RR between the monitors (0.1 breaths), for RR between the manually counted and the PICO or the monitor (respectively 0.2 and 0.0 breaths), also confirmed by the regression analysis (Passing-Bablok). Analysis of 219 ECG records provided a near perfect agreement between the devices (kappa respectively 0.61–0.80 and 0.81–1.00) for the most important ECG abnormalities. In none of the comparisons, differences were clinically relevant. Conclusion: We were able to confirm the analytical accuracy of the PICO monitor in comparison with the ED monitors. The PICO monitor can be considered a reliable device for monitoring patients during emergencies by GPs and even in ambulances or EDs as a mobile alternative.